Urban Governance in Sub‐Saharan Africa. For a geography of regulation - (:unkn) unknown (My University, 2002)
Implementation of governance principles entails intra-urban territorializations in sub- Saharan African cities, which increase the risks of fragmentation and raise the question of local scale regulation in both its political and spatial dimensions.
Keywords: African Research